2014
DOI: 10.1038/cddis.2014.419
|View full text |Cite
|
Sign up to set email alerts
|

Mcl-1 promotes lung cancer cell migration by directly interacting with VDAC to increase mitochondrial Ca2+ uptake and reactive oxygen species generation

Abstract: Mcl-1 is an antiapoptotic member of the Bcl-2 family frequently upregulated in non-small cell lung carcinoma (NSCLC). We now report the physiological significance of an interaction between Mcl-1 and the mitochondrial outer membrane-localized voltage-dependent anion channel (VDAC) in NSCLC cell lines. Mcl-1 bound with high affinity to VDAC1 and 3 isoforms but only very weakly to VDAC2 and binding was disrupted by peptides based on the VDAC1 sequence. In A549 cells, reducing Mcl-1 expression levels or applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
114
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(120 citation statements)
references
References 55 publications
5
114
1
Order By: Relevance
“…Finally, in contrast to our findings and those of others (26,62), recent reports indicated that anti-apoptotic Bcl-XL and Mcl-1 are both able to enhance VDAC1-mediated Ca 2ϩ transfer into the mitochondria under some conditions (51,63). Indeed, their overexpression enhanced while their deficiency suppressed mitochondrial Ca 2ϩ uptake (51,63).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Finally, in contrast to our findings and those of others (26,62), recent reports indicated that anti-apoptotic Bcl-XL and Mcl-1 are both able to enhance VDAC1-mediated Ca 2ϩ transfer into the mitochondria under some conditions (51,63). Indeed, their overexpression enhanced while their deficiency suppressed mitochondrial Ca 2ϩ uptake (51,63).…”
Section: Discussioncontrasting
confidence: 56%
“…Indeed, their overexpression enhanced while their deficiency suppressed mitochondrial Ca 2ϩ uptake (51,63). These effects were not observed in VDAC1-deficient cells and were counteracted by N-terminal VDAC1-derived peptides (51,63).…”
Section: Discussionmentioning
confidence: 81%
“…VDAC1 and VDAC2 are the main isoforms in most mammalian cells, including cancer cells in which they account for up to 90% of the total. The least abundant isoform, VDAC3, comprising the remaining 10% (De Pinto et al, 2010; Huang, Shah, Bradbury, Li, & White, 2014; Maldonado et al, 2013) is abundant only in testis (Sampson et al, 2001; Sampson, Lovell, & Craigen, 1997). …”
Section: Vdac Channels and Mitochondrial Metabolismmentioning
confidence: 99%
“…In NSCLC, Bcl-2, Bcl-xl and Mcl-1 are often found to be upregulated, which is associated with chemotherapy resistance and metastasis of cancers [11, 12]. These findings indicate that suppression of the anti-apoptotic Bcl-2 proteins may be a promising strategy for cancer therapy and potentially overcome the resistance to conventional chemotherapy.…”
Section: Introductionmentioning
confidence: 97%